2009
DOI: 10.1007/s10151-009-0474-6
|View full text |Cite
|
Sign up to set email alerts
|

Rectal diversion without colostomy in Fournier’s gangrene

Abstract: Fournier's gangrene is a potentially fatal necrotizing fasciitis affecting the perineum and genital area. The usual treatment includes prompt surgical debridement and, in many cases, a diverting colostomy. We present two cases of Fournier's gangrene that were treated with extensive local debridement and rectal diversion with a new device for faecal matter management, avoiding the need for a colostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…It was originally designed for intensive care patients with a rectal tube that allows diversion of faecal matter from the rectum to a collector bag. In this way, it avoids faecal leakage, and thus keeps the wound clean . In Fournier's gangrene, also, this system can successfully be used in an effort to achieve faecal diversion.…”
Section: Discussionmentioning
confidence: 98%
“…It was originally designed for intensive care patients with a rectal tube that allows diversion of faecal matter from the rectum to a collector bag. In this way, it avoids faecal leakage, and thus keeps the wound clean . In Fournier's gangrene, also, this system can successfully be used in an effort to achieve faecal diversion.…”
Section: Discussionmentioning
confidence: 98%
“…The device protects the wounds from fecal contamination and reduces the same way that a colostomy both the risk of skin breakdown and repeated inoculation with colonic flora. Estrada et al [42] showed that it was effective way for fecal diversion and forms an alternative to colostomy. It is recommended to explore the canal anal before placement of the catheter in order to avoid rectal injuries.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…In the literature, there are few reported cases regarding the use of Flexi-Seal Faecal Management System in Fournier's gangrene. Our approach differs from previous cases (3,4), with the combination of Flexi-Seal and NPWT, as presented here. This helped us to achieve faster wound healing.…”
mentioning
confidence: 90%